Optimalisasi peran penyuluh pertanian dalam pengembangan kapasitas petani di Tana Toraja - Parinding, Bertha; Mahmud, Musdalifah; Ibrahim, Helda (Journal of Agribusiness Science and Rural Development, 2025)
The current situation in Tana Toraja Regency indicates that the capacity of farmers in Tana Toraja needs to be continuously improved so they can optimize the potential of existing land and commodities. Agricultural extension programs in Tana Toraja have been and continue to be implemented, but the extent to which these programs contribute significantly to improving farmers' knowledge, skills, and attitudes still requires further in-depth study. Therefore, this research is relevant and urgent to comprehensively analyze the contribution of agricultural extension services in improving farmer capacity in Tana Toraja Regency, so that it can provide constructive input for the formulation of more effective extension policies and strategies in the future. This study used the Likert scale method, a method used to measure a person's attitudes, opinions, or perceptions of a statement. The sample in the study was taken using purposive sampling. The results showed that agricultural extension significantly contributed to increasing farmer capacity, both in terms of knowledge, skills, and attitude change. The questionnaire results showed that the average Likert score was in the high category (3.77–4.49) for all indicators. Farmers stated that they had a better understanding of rice cultivation techniques (average score 4.49), pest/disease control (4.29), and were more skilled in using agricultural machinery (3.77). Most farmers implemented the results of extension training on their land (4.49), experienced increased yields (4.43), and were motivated to continue learning and participating in training (4.49). Overall, agricultural extension training in this region has proven effective in increasing farmer capacity, particularly in terms of technical understanding, practical skills, and positive attitudes toward agricultural technology innovation. However, strategies are needed to increase the participation of inactive farmers and expand the scope of materials on marketing and processing of agricultural products.